Node positive breast cancer: Concordance between baseline PET/CT and sentinel node assessment after neoadjuvant therapy. (September 2019) - Christin, Oscar Leopoldo; Kuten, Jonathan; Even-Sapir, Einat; Klausner, Joseph; Menes, Tehillah S.
Abstract: Introduction: Sentinel node biopsy for axillary staging in node positive patients after neoadjuvant treatment is controversial, mainly due to high false negative rates. We examined the concordance between the location of the hot nodes identified on PET-CT at presentation with the location of the sentinel nodes. Materails and methods: Fifty-eight breast cancer patients undergoing neoadjuvant treatment between January 2013 and September 2018 who had positive regional lymph nodes on PET/CT, and a SPECT/CT lymphoscintigraphy completed before sentinel node biopsy were included. Patient, tumor and treatment characteristics were collected. Images of PET/CT were compared to images of SPECT/CT lymphoscintigraphy post treatment and concordance between location of the hot nodes on PET/CT with the sentinel nodes visualized on SPECT/CT was assessed. Association between patient, tumor and treatment characteristics and concordance between the sentinel node and the hot nodes was determined. Results: Sentinel nodes were identified in 53 (91%) of the cases in surgery. In 25 (43%) patients, axillary nodes were positive after treatment. In 16 (28%; 95% CI 18, 40) the sentinel node was not one of the hot nodes seen on PET/CT at presentation. Twenty-three (40%) patients had excision of additional axillary nodes. In two patients with non-concordant sentinel nodes, the sentinel node was falsely negative. Conclusions: In node positive patients who undergo neoadjuvant treatment, the sentinel node visualized on lymphatic mapping is not necessarily one of the hot nodes identified on PET/CT at presentation. These findings underline the importance of marking the pathologically proven lymph node and excising it as well as the sentinel nodes after treatment. Highlights: Concordance between FDG-avid and sentinel lymph nodes in breast cancer patients undergoing neoadjuvant treatment was assessed. In only 71% at least one of the hot nodes on the baseline PET/CT was found to be a sentinel node after neoadjuvant therapy. No association was found between type of cancer, treatment, response and concordance between the nodes on both studies. After neoadjuvant treatment, the sentinel node is not necessarily one of the hot nodes identified on PET/CT. These findings underline the importance of marking and excising pathological lymph node and the sentinel nodes after treatment.